1997
DOI: 10.1175/1520-0450(1997)036<0485:troscp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Retrieval of Stratocumulus Cloud Properties by Ground-Based Cloud Radar

Abstract: The radiative characteristics of stratocumulus clouds are dependent upon their microphysical properties, primarily the liquid water content and effective radius of the drop population. Aircraft observations of droplet spectra in warm stratocumulus over the North Atlantic and around the British Isles by the Hercules C-130 aircraft of the U.K. Meteorological Office Meteorological Research Flight have been used to calculate the radar reflectivity, liquid water content, and effective radius. Empirically derived re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 25 publications
2
87
0
1
Order By: Relevance
“…Whereas the presence of drizzle in clouds as an initial stage in the development of precipitation benefits the problem of detection, particularly for boundary layer clouds, it also complicates the estimation of cloud liquid water (e.g., Fox and Illingworth 1997). Although it may be straightforward to identify drizzle from a reflectivity threshold perspective (e.g., Frisch et al 1995) or from combinations of reflectivity and cloud optical depth (AUSTIN), retrieval of quantitative information about cloud LWC in the presence of drizzle have not been developed.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Whereas the presence of drizzle in clouds as an initial stage in the development of precipitation benefits the problem of detection, particularly for boundary layer clouds, it also complicates the estimation of cloud liquid water (e.g., Fox and Illingworth 1997). Although it may be straightforward to identify drizzle from a reflectivity threshold perspective (e.g., Frisch et al 1995) or from combinations of reflectivity and cloud optical depth (AUSTIN), retrieval of quantitative information about cloud LWC in the presence of drizzle have not been developed.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…This radar is calibrated to an accuracy of ≈1 dB. When drizzle drops are present in stratocumulus, these are expected to dominate the radar reflectivity (Fox and Illingworth, 1997). The drizzle structure is quite similar to the lidar, although the radar appears to pick up a wider coverage of very weak drizzle (reflectivities < −10 dBZ).…”
Section: Case Study I: Drizzling Stratocumulusmentioning
confidence: 99%
“…However, its role in the climatology of clouds on larger scales is controversial. Previous field programs have suggested that drizzle might be a relatively common phenomenon (e.g., Brost et al 1982;Duynkerke et al 1995;Fox and Illingworth 1997;Vali et al 1998) and, thus, could play a vital role in the evolution of the STBL (e.g., Paluch and Lenschow 1991). In this respect simple theoretical models (e.g., Albrecht 1989;Ackerman et al 1993;Wang and Albrecht 1986;Pincus and Baker 1994) suggest that the modulation of drizzle by changes in the atmospheric aerosol could regulate cloud amount and thickness.…”
Section: Drizzlementioning
confidence: 99%